2018
DOI: 10.1186/s12891-018-2354-6
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, skills and use of evidence-based practice among UK osteopaths: a national cross-sectional survey

Abstract: BackgroundEvidence-based practice (EBP) is a clinical decision-making framework that supports quality improvement in healthcare. While osteopaths are key providers of musculoskeletal healthcare, the extent to which osteopaths engage in EBP is unclear. Thus, the aim of this cross-sectional study was to investigate UK osteopaths’ attitudes, skills and use of EBP, and perceived barriers and facilitators of EBP uptake.MethodsUK-registered osteopaths were invited to complete the Evidence-Based Practice Attitude and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
57
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 50 publications
29
57
1
3
Order By: Relevance
“…Given that this survey was distributed to practicing osteopaths, most without academic or research affiliations, it should be expected that they use research findings rather than produce them. Again, our findings are similar to recent studies, where Malaysian physiotherapists [41], US chiropractors [32] and UK osteopaths [29] were found to be confident in information appraisal, but lacked research skills. The small percentage of osteopaths reporting high-level skill in conducting clinical research or systematic reviews was also similar to previous studies of US and Canadian chiropractors where less than 5 % of respondents reported a high level of skill in these areas [31, 32].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Given that this survey was distributed to practicing osteopaths, most without academic or research affiliations, it should be expected that they use research findings rather than produce them. Again, our findings are similar to recent studies, where Malaysian physiotherapists [41], US chiropractors [32] and UK osteopaths [29] were found to be confident in information appraisal, but lacked research skills. The small percentage of osteopaths reporting high-level skill in conducting clinical research or systematic reviews was also similar to previous studies of US and Canadian chiropractors where less than 5 % of respondents reported a high level of skill in these areas [31, 32].…”
Section: Discussionsupporting
confidence: 91%
“…They also reported moderate-to-high levels of self-perceived skill in the identification of clinical questions and knowledge gaps in practice, as well as appraising and applying evidence from research to their clinical practice. These findings were similar to the perceived EBP skill level reported by UK osteopaths [29]. Interestingly, respondents in the current study judged their skills in the relatively high-level tasks of ‘critical appraisal’ and ‘evidence synthesis’ to be of similar level as the more fundamental skill of ‘using findings from systematic reviews’.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the number of responses obtained are sufficient to verify if there is a difference between categories [38]. In fact, our numbers are similar or superior to those found in other surveys conducted among osteopaths in the UK [39], Quebec [8] or even similar to recent surveys conducted among physiotherapists in Germany [40], Saudi Arabia [41] or Australia [42]. Only the completion of a regulatory process and the creation of the mandatory official register will allow to exactly know the number of Spanish osteopaths.…”
Section: Limitationssupporting
confidence: 76%
“…Providing clarity on norms and expectations (Table 1), favouring exposure to rich clinic experiences, and shaping the culture of the profession would contribute to professional identity formation [38][39][40]. Some promising leads could be to open discussions about osteopathic principles, evidenceinformed education in osteopathy [41][42][43], considering opportunities for 'think tanks' to inform policymakers, reach agreement on models relying on quality consensus studies, include patient, practitioner and experts in discussions, and structure our research to focus on building our foundations [44]. Table 2 provides some suggested steps to put in place before proposing models of care in osteopathic education.…”
mentioning
confidence: 99%